Effect of Global Economic Liberalization on Manufacturing Firms in Muslim Areas in the Philippines - Eugenio J. Manulat (Philippine Institute for Development Studies (PIDS), 2005)
The study aimed at determining the effects of global economic liberalization on manufacturing industries in Muslim areas in the Philippines. A total of 103 respondents/manufacturers of the different manufacturing firms, who were either indirectly or directly involved in export or import business were the targets for the study. Majority of the respondents were aware of the liberalization process taking place and adjustments were taken by most manufacturing industries in the Muslim areas in the Philippines to counteract the negative effects of globalization. But further intervention should be made to enhance and support the manufacturing industries in the Muslim areas. Among them are resolution of the peace and order situation, credit facilitation, technical assistance, market access abroad, tax reduction and lower tariffs, and infrastructure facilities.
Keywords: 330; Islamic economy; economic liberalization; Muslim industries; Globalisierung; Deregulierung; Handelsliberalisierung; Industrie; Islam; Philippinen